History And Classification Of Articles In English, Russian, And Uzbek Languages - Abdullaha Munojot Mayliovna (Euro Asian Journal Publishing, 2024)
Despite the prevalence of oral creativity, this article provides information about the history of the article, its history of study in literature and linguistics, its research on European, Russian, and Uzbek linguists and researchers in the field of paremia and mathematics, as well as the works he has produced in the field of mathematics. At the same time, in the process of studying articles, articles can also have views of the model of a society 'fragment' that has a variety of forms that provide complete information about the life, mothers, history, and traditions of this people, which can be used by a number of visual tools, such as antithesis, anaphora, alliteration, cinema, and piching
Keywords: articles; paremia; phraseology; article characteristics